The Analysis Of Malaysian Domestic Travelers. - Mohamed, Badaruddin (2005)
Various crises, such as the Bali Bombing, the spread of SARS and the haze, among others, had left tremendous impacts on the tourism sector. After years of concentrated efforts to attract foreign tourists to visit this country, the Malaysian government has started to acknowledge the importance and the potential of domestic tourists.